How Ethanol Is Made from Cellulosic Biomass - Zhaohui Tong; Pratap Pullammanappallil; Arthur A. Teixeira (EDIS)
Ethanol can be derived from sugar-based, corn-based, and cellulose-based materials. Production of ethanol from sugar and corn is often viewed as competing with food production and increasing prices of food and fuel. But using non-edible cellulose-based biomass to produce ethanol minimizes competition with the food industry. This 4-page fact sheet provides a general overview of the production process for manufacturing ethanol from cellulosic biomass, including its constituents, conversion processes, and final products. Written by Zhaohui Tong, Pratap Pullammanappallil, and Arthur A. Teixeira, and published by the UF Department of Agricultural and Biological Engineering, November 2012.